2022
DOI: 10.1088/1361-6528/ac69f9
|View full text |Cite
|
Sign up to set email alerts
|

Visible light-driven photocatalytic activity of Cu2O/ZnO/Kaolinite-based composite catalyst for the degradation of organic pollutant

Abstract: Herein, we design to synthesize a novel Cu2O/ZnO/kaolinite composite catalyst by co-precipitation method. The synthesized composite catalysts were labeled as 5CZK, 10CZK, 15CZK, and 20CZK which represent 5, 10, 15, and 20% of Cu2O, respectively, on ZnO/kaolinite. The photocatalyst samples were characterized with different instruments. Moreover, the methylene blue (MB) dye was used as a target organic pollutant and the degradation was evaluated under visible light irradiation. The highest performance for the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Recently, photocatalysis has attracted tremendous attention in environmental remediation technology. , Different types of photocatalysts have been utilized for wastewater treatment using photocatalysis systems. Among them, ZnO is the most studied semiconductor due to its high stability, low cost, and nontoxicity . However, the wider band gap and higher recombination rates of the photogenerated charge carriers hinder its photocatalytic activity under visible light . Hence, the modification of ZnO with different techniques such as doping or heterojunction formation to inhibit the photogenerated charge carrier recombination rates and expand the visible light absorption ranges have been reported. According to previous reports, doping with copper is the best technique to improve photocatalytic efficiencies because of its unique interaction properties with ZnO .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, photocatalysis has attracted tremendous attention in environmental remediation technology. , Different types of photocatalysts have been utilized for wastewater treatment using photocatalysis systems. Among them, ZnO is the most studied semiconductor due to its high stability, low cost, and nontoxicity . However, the wider band gap and higher recombination rates of the photogenerated charge carriers hinder its photocatalytic activity under visible light . Hence, the modification of ZnO with different techniques such as doping or heterojunction formation to inhibit the photogenerated charge carrier recombination rates and expand the visible light absorption ranges have been reported. According to previous reports, doping with copper is the best technique to improve photocatalytic efficiencies because of its unique interaction properties with ZnO .…”
Section: Introductionmentioning
confidence: 99%
“… 20 However, the wider band gap and higher recombination rates of the photogenerated charge carriers hinder its photocatalytic activity under visible light. 21 Hence, the modification of ZnO with different techniques such as doping or heterojunction formation to inhibit the photogenerated charge carrier recombination rates and expand the visible light absorption ranges have been reported. 22 24 According to previous reports, doping with copper is the best technique to improve photocatalytic efficiencies because of its unique interaction properties with ZnO.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that the fabrication of ZnO nanowires using the hydrothermal method is simple and economical. Additionally, various fabrication techniques for mono-and binary structures, as well as ternary structures-including co-precipitation [32], hydrothermal [27], sol-gel [14], solution combustion [33], and plasma technology [28,34,35]-have been applied. Moreover, plasma technology has increasingly satisfied the urgent requirement for the development of a quick, easy, and eco-friendly approach.…”
Section: Introductionmentioning
confidence: 99%